2023
DOI: 10.3390/app131910945
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Assembled Beam–Column Connections with Modified Reactive Powder Concrete under Different Steel Fiber Types in the Critical Cast-in-Place Regions

Xin Wang,
Ding Huang,
Qian Gao
et al.

Abstract: Reactive powder concrete (RPC) and reinforcements have ultra-high bonding strength and, thus, a potential advantage in improving the connection performance of assembled structures. In this study, four assembled beam–column connections using modified reactive powder concrete (MRPC) under different steel fiber types in critical cast-in-place regions, as well as a monolithic concrete beam–column connection, were tested under low-cyclic loading. The results show that MRPC application in critical cast-in-place regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…For MSF and WSF mixes (Figure 18), the results were almost convergent with the MSF mix results being a little higher due to the higher surface area offered by the MSF, which increases the attached surfaces and the Interfacial Transition Zone (ITZ) and hence augments the resistance to the tensile loads by effectively transferring loads from the matrix to the fibers. The results are in accordance with [20][21][22]. Regarding the effect of different fibers on the splitting strength of RPC, the increase after 28 days of curing for AC was 24.75, 39.37, and 71.19% for WF-RPC, CF-RPC, and MF-RPC, respectively, while for CC it was 34.29, 50.4, and 59.75% for WF-RPC, CF-RPC, and MF-RPC, correspondingly, and for WC it was 32.89, 61.33, and 87.25%, respectively.…”
Section: Splitting Strengthsupporting
confidence: 90%
See 1 more Smart Citation
“…For MSF and WSF mixes (Figure 18), the results were almost convergent with the MSF mix results being a little higher due to the higher surface area offered by the MSF, which increases the attached surfaces and the Interfacial Transition Zone (ITZ) and hence augments the resistance to the tensile loads by effectively transferring loads from the matrix to the fibers. The results are in accordance with [20][21][22]. Regarding the effect of different fibers on the splitting strength of RPC, the increase after 28 days of curing for AC was 24.75, 39.37, and 71.19% for WF-RPC, CF-RPC, and MF-RPC, respectively, while for CC it was 34.29, 50.4, and 59.75% for WF-RPC, CF-RPC, and MF-RPC, correspondingly, and for WC it was 32.89, 61.33, and 87.25%, respectively.…”
Section: Splitting Strengthsupporting
confidence: 90%
“…The inclusion of steel fibers leads to a considerable increase in tensile strength, while the addition of steel fibers causes a slight increase in compressive strength as the fiber volume fraction rose from 0% to 3%. Authors in [20] concluded that straight steel fibers were easily pulled out and had the least inhibitory effect on cracks. Connections using wavy steel fibers had the lowest initial stiffness and shear capacity, but the highest energy dissipation capacity.…”
Section: Introductionmentioning
confidence: 99%